Factors influencing sport development among women with disabilities: a case study of a visually impaired Spanish Paralympic woman - Barrera-Garcimartín, Alejandro; Redondo-Fernández, Áurea; Pérez-Tejero, Javier (Frontiers in Sports and Active Living, 2025)
IntroductionWomen with disabilities may experience particular difficulties in starting and developing in sport, also in the Paralympic context. Although a great deal of research has been conducted with high-performance athletes, relatively few studies have focused on athletes with disabilities, especially Paralympic women using person-first approaches. Thus, the main objective of this study is to understand, through the experience and opinion of a Paralympian female athlete, how these athletes reach their full potential, identifying the elements and initiatives that can influence (whether positively or negatively) their sporting trajectory and developmental milestones.MethodologyThis study analyzes the case of a quadruple Paralympic medalist in blind Judo, who has competed in Paralympic Games from Athens 2004 to Paris 2024. Information was gathered from a semi-structured interview, a book chapter she had written, and her participation in a forum.ResultsThe athlete differentiated between two key stages in the sports career of people with disabilities: (1) the beginning of sports practice; and (2) development processes and the search for future Paralympic athletes. Women with disabilities face particular difficulties in accessing sport, with foundations for people with disabilities and coaches playing a fundamental role. It is crucial to give visibility and have sports references in these areas, highlighting initiatives such as Paralympic School Days and inclusive competitions. There are conditioning factors in the identification and development of talent, such as the rules and the nature of each Paralympic sport, and the level of inclusion that the athletes have experienced in their environment.ConclusionsThis case study presents the perceptions of a female athlete with regard to the beginnings and development of sport in the Paralympic framework, underlining the need to promote actions that help and encourage the development and participation of women with disabilities in sport.